The no. 1 ladies' detective agency - McCall Smith, Alexander, 1948- (No. 1 Ladies' Detective Agency, 2003)
Precious Ramotswe has only just set up shop as Botswana's No.1 (and only) lady detective when she is hired to track down a missing husband, uncover a con man, and follow a wayward daughter.However, the case that tugs at her heart, and lands her in danger, is a missing eleven-year-old boy, who may have been snatched by witch doctors.